GABA in, garbage out: AIS-located proteasomes regulate the developmental GABA switch - Leterrier, Christophe (J Cell Biol, 2020)
The GABA response switch from excitatory to inhibitory is a key event in neuronal maturation that depends on the regulated expression of chloride transporters NKCC1 and KCC2. In this issue, Lee et al. (2020. J. Cell. Biol. https://doi.org/10.1083/jcb.201903033) describe how degradation of NKCC1 by proteasomes immobilized at the axon initial segment (AIS) by the Ecm29 adaptor contributes to this regulation, driving the GABA switch and the positional maturation of the AIS.